Number of attempts required by emergency physicians to achieve competency in diaphragmatic ultrasound imaging. Issue 2 (31st December 2021) - Puchongmart, Chanokporn; Nakornchai, Tanyaporn; Rittayamai, Nuttapol; Monsomboon, Apichaya; Prapruetkit, Nattakarn; Limsuwat, Chok; Ruangsomboon, Onlak; Chakorn, Tipa
Abstract: Purpose: This research aimed to determine the number of attempts that emergency physicians need to become proficient in undertaking diaphragmatic ultrasound imaging. Methods: A prospective observational study was conducted at the emergency department (ED) of a tertiary‐care university hospital. Sixteen emergency physicians were each required to obtain a set of images of the right hemidiaphragm of five dyspneic patients using both diaphragmatic excursion and thickness techniques. The images were subsequently reviewed by a specialist using American College of Emergency Physician guidelines. If the evaluations of a physician did not reach the expected standard, the physician was to be given feedback and requested to collect images from another five patients. The process was to be repeated until such time as the images obtained by the physician were deemed to be up to standard. Results: Eighty patients, twelve emergency medicine residents, and four attending physicians were enrolled. Following a didactic session on diaphragmatic ultrasound imaging and its interpretation, practicing on five patients proved sufficient to achieve an adequate level of competency in conducting diaphragmatic ultrasound examinations. Conclusion: Practicing on five patients is sufficient for emergency physicians to achieve an adequate level of competency in conducting right‐sided diaphragmatic ultrasound examinations. Abstract : A prospective observational study of diaphragmatic ultrasound training was conducted at the emergency department of a tertiary care university hospital. The training included a teaching session and data collection on diaphragmatic excursion and thickness techniques in dyspneic patients. We found that practicing on five patients is sufficient for emergency physicians to achieve an adequate level of competency in conducting diaphragmatic ultrasound examinations.